A high-performance supportless silver nanowire catalyst for anion exchange membrane fuel cells. Issue 4 (11th December 2014) - Zeng, L.; Zhao, T. S.; An, L.
Abstract : The use of supportless Ag NWs enabled the H2 /O2 AEMFC to yield a peak power density of 164 mW cm −2 . Abstract : Silver has been widely investigated as a cathode catalyst owing to its stable and high electrocatalytic activity in anion exchange membrane fuel cells (AEMFCs). In this work, we synthesize silver nanowires (Ag NWs) using the polyol synthesis method and demonstrate that the supportless Ag NWs exhibit an extraordinarily high electrocatalytic activity toward the oxygen reduction reaction in a three-electrode cell. More significantly, the use of supportless Ag NWs as the cathode catalyst in a H2 /O2 AEMFC yields a peak power density of 164 mW cm −2 at 60 °C, which is favorably comparable to the state-of-the-art AEMFCs with carbon-supported Ag catalysts. In addition to the increased electrocatalytic activity, the improved performance is attributed to the elongated wire morphology of Ag NWs which allows a well-established porous electrode structure to form in the cathode. The high-performance supportless Ag NWs offer a promising alternative to carbon-supported electrocatalysts in fuel cells and metal–air batteries, to eliminate the carbon supporting materials.